Analysis Of Students' Errors In Solving Geometric Transformation Problems At Sma Amir Hamzah Medan - Annisa Qoyyima; Elisabeth Romauli Purba; Maria Panjaitan; Tabitha Gabriela Sianipar; Kms. Muhammad Amin Fauzi (PT. Padang Tekno Corp, 2025)
This study aims to analyze the types of errors made by 11th grade students at SMAS Amir Hamzah Medan in solving geometric transformation problems involving translation, reflection, rotation, and dilation. The study employs a qualitative descriptive approach with a sample of 15 students selected based on high, medium, and low ability categories. Data were collected through essay tests and analyzed using Newman's Error Analysis, which consists of five stages of errors: reading, understanding, transformation, process skills, and writing the final answer. The analysis results indicate that the highest incidence of errors occurred in the understanding stage and process skills stage, each accounting for 36%. Transformation errors accounted for 21.33%, while reading and final answer writing errors were in the very low category, each at 9.33%. These findings indicate that students still face difficulties in understanding basic concepts and technical steps in geometric transformations. Based on these results, it is recommended that teachers implement systematic learning strategies such as Learning Therapy, emphasizing the understanding of prerequisite concepts, writing down known and asked information, and developing the habit of structuring and evaluating solution steps systematically to minimize similar errors in the future.